Preferensi Masyarakat Dalam Memilih Bank di Situ Udik, Cibungbulang, Bogor - Rinaldi Septiana; Rio Kartika Supriyatna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
The purpose of this study is to determine and analyze the magnitude of the effect of expectations and benefits on motivation partially and simultaneously. Analyze the effect of expectations and benefits on decisions. Analyzing the effect of expectations and benefits on decisions through intervening variables.This research is quantitative. Data collection method is to use primary data through a questionnaire to the people of Situ Udik Village with a sample size of 96 respondents. The analysis used is path analysis. The results of the study in regression 1 showed that partialy and simultaneously the expectation variable had a real positive effect on people's motivation. The model regression test shows that the expectation variable has no effect on motivation. Simultaneously shows the expectation and profit variables have a significant positive effect on motivation. The influence of expectations on decisions proves that there is no direct influence on decisions. Analysis of the effect of profits on decisions proves that there is a significant influence on decisions. In the analysis of the influence of expectations on decisions through motivation shows there is a significant effect, on the profit variable, there is an influence on decisions through motivation as a connecting variable.